Methods to manage, protect and improve plant virus resistance - Tien Phat, Do; Bich Ngoc, Pham; Hoang Ha, Chu (Vietnam Journal of Biotechnology, 2021)
Viral diseases caused severe damage for plant growth and development. Penetration and spread of viruses in the host plants dramatically reduce crop yield and quality. Due to the critical damages of viral diseases to agricultural production, different approaches and methods have been developed and utilized to manage, protect and improve plant virus resistance. Of which, conventional methods such as meristem culture, thermotherapy, cryotherapy as well as chemotherapy have been widely used and conducted effective results. Moreover, cross protection and gene pyramiding approaches have performed the broad and stable spectrum resistance potential in different plant species. Recently, advanced methods like plant transformation, gene silencing as well as genome editing have shown great successes in plant virus resistant improvement. In this review, we will briefly introduce the principle, advantages and limitations of different methods used for plant viral diseases management and viral resistant improvements. In addition, we will also discuss the challenges and future aspects in utilizing advanced technologies for plant virus resistant enhancement and breeding.